Kegiatan Seminar dan Menanam Pohon Menuju Kota Hijau di Kelurahan Danga Kecamatan Aesesa Kabupaten Nagekeo - Aurelius Fredimento; Laurentius Dominicus Gadi Djou; Sri Wahyuni (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2022)
One of the core activities to save the mother earth is by planting trees in barren places. The growth of trees that will become forests. The forest trees will reduce the impact of global warning, the availability of sufficient oxygen and water for the living creature, absorb the air pollution, adding the environmental nutrients, animal shelter, flood and erosion prevention. Based on the above ideas, the Group of Catholic Student of St. Martinus Ende which well known as KMK (Kelompok Mahasiswa Katolik) in collaboration with the Danga residents, in Nagekeo District planting trees around the city of Danga. The goal is to turn Danga as the capital city into a green city. This activity has been running from December 22 to December 29, 2021. This activity is also carried out using two methods. First, holding a one-day seminar to build an understanding of the environment, the benefits of the living environment, and how to care for and maintain the environment. The second is tree planting activities.